2014
DOI: 10.1152/ajplung.00001.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sustained hyperoxia-induced NF-κB activation improves survival and preserves lung development in neonatal mice

Abstract: Oxygen toxicity contributes to the pathogenesis of bronchopulmonary dysplasia (BPD). Neonatal mice exposed to hyperoxia develop a simplified lung structure that resembles BPD. Sustained activation of the transcription factor NF-κB and increased expression of protective target genes attenuate hyperoxia-induced mortality in adults. However, the effect of enhancing hyperoxia-induced NF-κB activity on lung injury and development in neonatal animals is unknown. We performed this study to determine whether sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…These data support the idea of activating sGC as a management strategy in hyperoxia-induced lung injury. Along similar lines, McKenna and coworkers (231) demonstrated that sustained NF-B activation, through overexpression of the NF-B inhibitor-␤ (I-B␤), protected mice against the deleterious effects of hyperoxia (95% O 2 ) on alveolarization (assessed by MLI and RAC), suggesting that the potentiation of NF-B activity may also represent a management strategy in hyperoxia-induced lung injury.…”
Section: New Mediators and Modulators Of Impaired Alveolarizationmentioning
confidence: 88%
“…These data support the idea of activating sGC as a management strategy in hyperoxia-induced lung injury. Along similar lines, McKenna and coworkers (231) demonstrated that sustained NF-B activation, through overexpression of the NF-B inhibitor-␤ (I-B␤), protected mice against the deleterious effects of hyperoxia (95% O 2 ) on alveolarization (assessed by MLI and RAC), suggesting that the potentiation of NF-B activity may also represent a management strategy in hyperoxia-induced lung injury.…”
Section: New Mediators and Modulators Of Impaired Alveolarizationmentioning
confidence: 88%
“…Hyperoxia is a significant cause of lung injury and contributes to the pathogenesis of BPD. 14,15 The hallmark features of BPD are a decreased number of alveoli, increased variability in alveolar size, and lung interstitial fibrosis. 3,16 There is evidence from animal models that exposure of the developing lung to hyperoxia leads to the development of a simplified lung structure that resembles human BPD.…”
Section: Discussionmentioning
confidence: 99%
“…3,16 There is evidence from animal models that exposure of the developing lung to hyperoxia leads to the development of a simplified lung structure that resembles human BPD. 15 A Figure 3 Growth curve of 5-aza-CdR-treated LFs (n Z 5).…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic potential of NF-kB inhibition is limited by its essential role in physiologic lung development, mediating both alveologenesis and vasculogenesis. Furthermore, a disease-limiting function of NF-kB in inflammation was attributed to the suppression of macrophage inflammatory protein 2 [ 50 53 ]. The physiologic functions of NF-kB in the developing lung are even more complex as it is ubiquitously expressed; controls diverse cellular functions including apoptosis, survival, proliferation, and immune regulation; and exerts simultaneously pro- and anti-inflammatory actions.…”
Section: The Pulmonary Inflammatory Responsementioning
confidence: 99%